2019
DOI: 10.1088/1742-6596/1320/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Affecting the Health Insurance Ownership with Binary Logistic Regression Model

Abstract: Having health insurance is an important decision for enjoying the security of a safe future. Health insurance can protect people from a large amount of medical costs. More Indonesian have health insurance now a days than ever before since the government is committed to supporting the universal health care. This study aims to determine factors affecting the health insurance ownership and to understand their relations in Indonesia using a binary logistic regression model. The data used in this study came from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…The diagnostic tests in Table 4 indicate that the model is statistically significant at the 1% level. Though the pseudo R-squared (Cox & Snell = 0.079; Nagelkerke = 0.145) appear low, they are nonetheless in line with the values reported byAziz et al (2017) andAstari and Kismiantini, (2019). The percentage of correct prediction indicates that 86% can be accurately predicted by the model.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…The diagnostic tests in Table 4 indicate that the model is statistically significant at the 1% level. Though the pseudo R-squared (Cox & Snell = 0.079; Nagelkerke = 0.145) appear low, they are nonetheless in line with the values reported byAziz et al (2017) andAstari and Kismiantini, (2019). The percentage of correct prediction indicates that 86% can be accurately predicted by the model.…”
supporting
confidence: 73%
“…This study used a binary logistic regression model, which is a probability model used when the dependent variable is a binary variable, while the independent variables are either categorical or scale variables (Rahji and Fakayode, 2009). Since the physical capital stock of NHEs is a dichotomous indicator variable, we followed the modelling approach of Astari and Kismiantini, (2019). Let π denote the physical capital stock of NHEs, while X i denotes the set of explanatory variables, which are either continuous or categorical variables.…”
Section: B Model Specificationmentioning
confidence: 99%
“…Since the controlled variable of this study, which is academic achievement, is a measurement variable categorised into two forms (i.e. it is a dichotomous variable), this study adopted the modelling technique of Astari and Kismiantini (2019). In the binary logit model adopted for this study, is used to represent the academic achievement of employees in Nigerian universities, while Xi is used to show the set of covariate variables, which are either continuous or categorical variables.…”
Section: Model Specification and Resultsmentioning
confidence: 99%
“…A similar result was found in other studies done in Bhaktapur by Karanjit P et al 4 Some of the studies showed significantly positive findings of marital status and enrolment in insurance schemes. [10][11][12] Enrollment of family in SHSS makes it secure and prevents out-of-pocket expenditure. Most of the enrolled family was nuclear family 76.6%, Similarly, two out of three had nuclear families found in the study of Sushmita G et al 8 The study by Sanjeeb S et al showed that 55% of families were nuclear .…”
Section: Discussionmentioning
confidence: 99%